2001
DOI: 10.1046/j.1432-1327.2001.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid composition of chylomicron remnants influences their binding and internalization by isolated hepatocytes

Abstract: The binding and internalization of 125 I-labelled chylomicron remnants derived from palm, olive, corn, or fish oil (rich in saturated, monounsaturated, n-6, or n-3 polyunsaturated fatty acids, respectively) by hepatocytes from rats fed a low-fat diet or a diet supplemented with the corresponding fat for 21 days was investigated. In hepatocytes from rats fed the low-fat diet, the association of radioactivity with the cells at 4 8C (a measure of initial binding only) was similar with all types of remnants tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
2
21
0
1
Order By: Relevance
“…Since we have shown previously that CMRs derived from palm, olive or corn oil are taken up at similar rates by hepatocytes [10,11], it seems unlikely that this effect can be explained by a decreased rate of uptake of the particles enriched in MUFAs. However, our earlier studies have shown that a greater proportion of the TAG taken up by the tissue from CMRs derived from olive as compared with corn or palm oil is used for oxidation [10], thus it is possible that less fatty acid from the olive oil CRLPs is available for TAG production.…”
Section: Discussionmentioning
confidence: 82%
“…Since we have shown previously that CMRs derived from palm, olive or corn oil are taken up at similar rates by hepatocytes [10,11], it seems unlikely that this effect can be explained by a decreased rate of uptake of the particles enriched in MUFAs. However, our earlier studies have shown that a greater proportion of the TAG taken up by the tissue from CMRs derived from olive as compared with corn or palm oil is used for oxidation [10], thus it is possible that less fatty acid from the olive oil CRLPs is available for TAG production.…”
Section: Discussionmentioning
confidence: 82%
“…The S f 60-400 TRLs are not a homogeneous fraction but contain a mixture of large VLDLs, small chylomicrons, and chylomicron remnants (43), and LRP1 is thought to play a significant role in the uptake of chylomicron remnants (41). A recent animal study that observed a slower uptake of chylomicron remnants enriched in SFAs by isolated rat hepatocytes compared with n-6 and n-3 PUFAs proposed that this was attributable to the influence of remnant fatty acid composition on the expression and/or activity of the LDL and LRP1 receptors (44).…”
Section: Discussionmentioning
confidence: 99%
“…For the lipids in remnants to affect the fatty acids of lipids in hepatocytes, the particles must have interacted with the cells, and their components internalised, metabolised and incorporated. It was recently observed that remnants from fish oil are internalised more rapidly than corn oil remnants at low, but not at high, remnant concentrations (20). Based on the uptake rates given in (20), at the concentrations of remnants used in the present study, it is likely that after six hours both the fish and the corn oil particles were processed completely by the hepatocytes.…”
Section: Discussionmentioning
confidence: 46%
“…It was recently observed that remnants from fish oil are internalised more rapidly than corn oil remnants at low, but not at high, remnant concentrations (20). Based on the uptake rates given in (20), at the concentrations of remnants used in the present study, it is likely that after six hours both the fish and the corn oil particles were processed completely by the hepatocytes. In our treated cells, triacylglycerol and phospholipid levels increased in a dosedependent manner, but while triacylglycerols incorporated the PUFA predominating in each remnant type, the fatty acid profile of phospholipids was virtually unaffected.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation